Promoting citizen-based river groups at sub-basin scale for multi-level river governance in the Barcelona Metropolitan Region. Issue 2 (1st February 2021) - Vall-Casas, Pere; Benages-Albert, Marta; Garcia, Xavier; Cuéllar, Alvaro; Pavon, David; Ribas, Anna
ABSTRACT: There is a gap between the increasing social use of urban rivers and limited citizen participation in river management under the EU Water Framework Directive (WFD). A pilot participatory process aimed at promoting the active involvement of the general public in the management of an urban stream in the Barcelona Metropolitan Region was designed and tested. The participatory process was supported by web-based Public Participation Geographic Information Systems and face-to-face workshops. The opinions of the general public were collected and citizen decision-making and self-organisation were promoted. Assessment of the pilot results provided key learning points supporting the creation of citizen-based river groups: (1) setting participation in the framework of a socio-ecological understanding of the river; (2) involving local volunteers in the leadership and dissemination of participatory processes; (3) supporting participants' learning and networking; and (4) connecting municipal-scale and basin-scale environmental interests and institutions through intermediate citizen platforms at sub-basin scale. These learning points offer a baseline for building a theory on the design of bottom-up participatory processes aimed at empowering riparian communities. Citizen-based river group formation policies may support the transition towards more multi-level European river governance.